Household Finance and Consumption Survey: Results from the 2021 wave (European Central Bank (ECB), 2023)
This report summarises the stylized facts from the fourth wave of the Eurosystem Household Finance and Consumption Survey, which provides household-level data collected in a harmonised way in all 19 euro area countries, as well as in the Czech Republic, Croatia and Hungary for a sample of more than 83,000 households. Although the survey does not refer to the same time period in all countries, the most common reference period for the data is 2021. The report presents results on household assets and liabilities, income, and indicators of consumption and credit constraints.
Keywords: D12; D14; D31; 330; Household-level data; assets; liabilities; wealth; financial pressure; consumption